Biomaterials as a Vital Frontier for Stem Cell-Based Tissue Regeneration - Nugud, Ahmed; Alghfeli, Latifa; Elmasry, Moustafa; El-Serafi, Ibrahim; El-Serafi, Ahmed T. (Frontiers in Cell and Developmental Biology, 2022)
Biomaterials and tissue regeneration represent two fields of intense research and rapid advancement. Their combination allowed the utilization of the different characteristics of biomaterials to enhance the expansion of stem cells or their differentiation into various lineages. Furthermore, the use of biomaterials in tissue regeneration would help in the creation of larger tissue constructs that can allow for significant clinical application. Several studies investigated the role of one or more biomaterial on stem cell characteristics or their differentiation potential into a certain target. In order to achieve real advancement in the field of stem cell-based tissue regeneration, a careful analysis of the currently published information is critically needed. This review describes the fundamental description of biomaterials as well as their classification according to their source, bioactivity and different biological effects. The effect of different biomaterials on stem cell expansion and differentiation into the primarily studied lineages was further discussed. In conclusion, biomaterials should be considered as an essential component of stem cell differentiation strategies. An intense investigation is still required. Establishing a consortium of stem cell biologists and biomaterial developers would help in a systematic development of this field.